IDDF2022-ABS-0013 Comparing diagnostic performance of cantonese-chinese version of rome iv criteria and a short reference standard for functional dyspepsia. (2nd September 2022) - Ho, Leonard; Chen, Shuijiao; Ho, Fai-Fai; Wong, Charlene HL; Ching, Jessica YL; Cheong, Pui-Kuan; Wu, Irene XY; Liu, Xiaowei; Leung, Ting-Hung; Wu, Justin CY; Chung, Vincent CH
Abstract : Background: Functional dyspepsia (FD) is diagnosed based on self-reported symptoms and negative upper gastrointestinal endoscopic findings. The Rome criteria were not adopted as a diagnostic instrument in clinical guidelines due to their complexity. Different guidelines used relatively simple symptom assessment schemes with contents that vary significantly. A previously evaluated short Reference Standard may serve as a more standardised tool for guidelines. We evaluated its diagnostic accuracy against the Rome IV criteria in a cross-sectional study in Hong Kong. Methods: A total of 220 dyspeptic patients sampled consecutively from the Hong Kong Prince of Wales Hospital and the community completed the Rome IV diagnostic questionnaire, which was translated into Cantonese-Chinese, along with the Reference Standard for FD. Sensitivity, specificity, positive and negative likelihood ratios (LRs), and area under the receiver operating characteristics curve (AUC), with 95% confidence intervals (CIs), were calculated. Results: Among the participants, 160 (72.7%) fulfilled the Reference Standard with negative upper gastrointestinal endoscopic results (IDDF2022-ABS-0013 Figure 1. Flow of study participants). The Reference Standard identified patients with Rome IV-defined FD with 91.1% (95% CI: 82.6%–96.4%) sensitivity and 37.6% (95% CI: 29.6%–46.1%) specificity. The positive and negative LRs were 1.46 (95% CI: 1.26–1.69) and 0.24 (95% CI: 0.11–0.49), respectively. The AUC value was 0.64 (95% CI: 0.59–0.69). Details on the diagnostic performance of the Reference Standard are illustrated in Table 1(IDDF2022-ABS-0013 Table 1). Conclusions: The Reference Standard can rule out patients without Rome IV-defined FD. It may be used as an initial screening tool for FD in settings where the use of the Rome IV criteria is impractical. It may also provide a uniform definition and diagnostic rule for future updates of clinical guidelines.